2017
DOI: 10.1016/j.ijvsm.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

A controlled study to investigate anti-diarrhoeal effect of the stem-bark fractions of Terminalia avicennioides in laboratory animal models

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…The CABAE administration significantly protected against all castor oil–induced deregulation of oxidative stress parameters in a dose‐dependent manner and returned their levels to near normal with the highest dose. In the same context, the implication of oxidative stress in the castor oil–induced intestinal hypersecretion was previously reported in many studies leading to an excessive ROS production such as O 2 •− , ROO • , HOCl, and OH• 2‐70 …”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The CABAE administration significantly protected against all castor oil–induced deregulation of oxidative stress parameters in a dose‐dependent manner and returned their levels to near normal with the highest dose. In the same context, the implication of oxidative stress in the castor oil–induced intestinal hypersecretion was previously reported in many studies leading to an excessive ROS production such as O 2 •− , ROO • , HOCl, and OH• 2‐70 …”
Section: Discussionsupporting
confidence: 60%
“…Antidiarrheal properties and GIT inhibition were previously reported for many medicinal plant extracts, such as Matricaria recutita , 2 Myrtus communis , 10 Ceratonia siliqua , 69 and Salvia officinalis 34 . Clonidine and yohimbine, used as reference molecules, respectively, inhibited and stimulated the GIT 10‐69 …”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Atropine is a competitive antagonist of acetylcholine muscarinic receptor [28] located on the intestinal smooth muscle. The activation of these receptors induces the production of the second messengers IP 3 and Diacyl glycerol (DAG) which are responsible for the increase of cytosolic calcium and smooth muscle contraction [11, 29, 30]. Like in the ethanolic extract of Bixa Orellana [14], phytochemical studies of the hydroethanolic extract revealed the presence of flavonoids, triterpenes, and tannins.…”
Section: Discussionmentioning
confidence: 99%
“…The method used by Suliman et al [ 26 ] was used to evaluate the activity of the crude extract on castor oil-induced intestinal fluid accumulation. The mice were assembled and treated in the same way as described above.…”
Section: Methodsmentioning
confidence: 99%